2016
DOI: 10.1017/s1049023x16001199
|View full text |Cite
|
Sign up to set email alerts
|

Health Service Impact from Mass Gatherings: A Systematic Literature Review

Abstract: Methods: A handheld GE V-Scan™ with Dual Probe ultra-sound was available for use by physicians in the main medical tent. All treating physicians consented to participate and self-reported their training and proficiency using POCUS. After each use of POCUS, physicians completed a survey recording the indication, scans performed, and impact on diagnosis, management, and disposition of patients. Results: In total, POCUS was used on 28 patients out of the 686 patients seen in the main medical tent. The three most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 37 publications
2
25
0
1
Order By: Relevance
“…To minimise impacts on EDs several strategies have been implemented in the pre‐hospital setting. These strategies may be considered in terms of: (i) specific patient groups, such as low acuity patients, high acuity patients, or people with mental health problem; or (ii) patients requiring care at particular times such as during peak periods of ED crowding, or during mass gathering events (MGEs) . A MGE is defined as an event where a group of people come together for a common purpose within a particular space or venue.…”
Section: Introductionmentioning
confidence: 99%
“…To minimise impacts on EDs several strategies have been implemented in the pre‐hospital setting. These strategies may be considered in terms of: (i) specific patient groups, such as low acuity patients, high acuity patients, or people with mental health problem; or (ii) patients requiring care at particular times such as during peak periods of ED crowding, or during mass gathering events (MGEs) . A MGE is defined as an event where a group of people come together for a common purpose within a particular space or venue.…”
Section: Introductionmentioning
confidence: 99%
“…Health services are often available to participants of a MGE within a staged approach, mirroring a patient journey from a MGE to an ED (Fig. ) . Each step in this approach increases the clinical resources and capacity of health provision.…”
Section: Introductionmentioning
confidence: 99%
“…The literature is superficial on reports of the impact of MGEs on ambulance usage and ED visits. In a systematic literature review exploring the health service impact from 24 different types of MGEs, variation was noted in the type of reporting of the impacts of MGEs on ambulance usage and ED visits . The literature review reported that the transport to hospital rate from a MGE is approximately 1/1000 participants .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations